The theatricality of the security system and the potentiality of the living. : Inquiries about Chácara Paraíso (2007) by Lola Arias and Stefan Kaegi - Cobello, Denise (Ephemera: Revista do Programa de Pós-Graduação em Artes Cênicas da Universidade Federal de Ouro Preto, 2024)
In the light of the notions of territory, testimony and life this work sets out to investigate contemporary documentary stage production, observing ruptures and continuities with a tradition of historical documentary theatre. Since the aesthetic-political renewal presented that emerged in the 2000’s, the deepening of the crisis of representation in art has led to a growing interest in the concept of the real that has allowed the reinvention of forms that put in tension the technologies of biopower through the imperceptible germs of life that emerge from its interstices.